Changes in chromatin accessibility are not concordant with transcriptional changes for single‐factor perturbations. Issue 9 (7th September 2022) - Kiani, Karun; Sanford, Eric M; Goyal, Yogesh; Raj, Arjun
Abstract: A major goal in the field of transcriptional regulation is the mapping of changes in the binding of transcription factors to the resultant changes in gene expression. Recently, methods for measuring chromatin accessibility have enabled us to measure changes in accessibility across the genome, which are thought to correspond to transcription factor‐binding events. In concert with RNA‐sequencing, these data in principle enable such mappings; however, few studies have looked at their concordance over short‐duration treatments with specific perturbations. Here, we used tandem, bulk ATAC‐seq, and RNA‐seq measurements from MCF‐7 breast carcinoma cells to systematically evaluate the concordance between changes in accessibility and changes in expression in response to retinoic acid and TGF‐β. We found two classes of genes whose expression showed a significant change: those that showed some changes in the accessibility of nearby chromatin, and those that showed virtually no change despite strong changes in expression. The peaks associated with genes in the former group had lower baseline accessibility prior to exposure to signal. Focusing the analysis specifically on peaks with motifs for transcription factors associated with retinoic acid and TGF‐β signaling did not reduce the lack of correspondence. Analysis of paired chromatin accessibility and gene expression data from distinct paths along the hematopoietic differentiation trajectory showed a much stronger correspondence, suggesting that the multifactorial biological processes associated with differentiation may lead to changes in chromatin accessibility that reflect rather than driving altered transcriptional status. Together, these results show many gene expression changes can happen independently of changes in the accessibility of local chromatin in the context of a single‐factor perturbation. Synopsis: Systematic analysis of tandem, bulk ATAC‐seq and RNA‐seq measurements from cells exposed to single‐factor perturbations shows two groups of genes: those with concordance between accessibility and expression changes and those without. MCF‐7 cells exposed to retinoic acid or TGF‐β have genes that show high expression changes without changes in local chromatin. By comparison, data from hematopoietic differentiation show much more concordance between chromatin accessibility changes and gene expression changes. Genes in the single‐factor perturbation data set that demonstrated more concordance had peaks that were less accessible at baseline prior to retinoic acid or TGF‐β exposure. Abstract : Systematic analysis of tandem, bulk ATAC‐seq, and RNA‐seq measurements from cells exposed to single‐factor perturbations shows two groups of genes: those with concordance between accessibility and expression changes and those without.